2018
DOI: 10.1038/s41467-018-03955-w
|View full text |Cite|
|
Sign up to set email alerts
|

Small GTPases and BAR domain proteins regulate branched actin polymerisation for clathrin and dynamin-independent endocytosis

Abstract: Using real-time TIRF microscopy imaging, we identify sites of clathrin and dynamin-independent CLIC/GEEC (CG) endocytic vesicle formation. This allows spatio-temporal localisation of known molecules affecting CG endocytosis; GBF1 (a GEF for ARF1), ARF1 and CDC42 which appear sequentially over 60 s, preceding scission. In an RNAi screen for BAR domain proteins affecting CG endocytosis, IRSp53 and PICK1, known interactors of CDC42 and ARF1, respectively, were selected. Removal of IRSp53, a negative curvature sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 71 publications
2
81
1
Order By: Relevance
“…However, whereas in vitro Cdc42 has been shown to enhance endocytic pathways via the regulation of the actin cytoskeleton (Georgiou et al, 2008;Leibfried et al, 2008;Sathe et al, 2018), in the acinar cells of salivary glands in vivo we found that it negatively regulates this process. Indeed, downregulation of Cdc42 induced a robust internalization of the membrane-targeted reporter mGFP, that is localized both at the basolateral and apical PM under control conditions.…”
Section: Cdc42 Depletion Impairs the Formation Of Ic Postnatallycontrasting
confidence: 58%
“…However, whereas in vitro Cdc42 has been shown to enhance endocytic pathways via the regulation of the actin cytoskeleton (Georgiou et al, 2008;Leibfried et al, 2008;Sathe et al, 2018), in the acinar cells of salivary glands in vivo we found that it negatively regulates this process. Indeed, downregulation of Cdc42 induced a robust internalization of the membrane-targeted reporter mGFP, that is localized both at the basolateral and apical PM under control conditions.…”
Section: Cdc42 Depletion Impairs the Formation Of Ic Postnatallycontrasting
confidence: 58%
“…5a ). In contrast, AP2 shRNA treatment of AGS cells that exhibit a bonafide CG pathway 38 only reduced TfR uptake while fluid uptake was increased (Supplementary Fig. 5b ).…”
Section: Resultsmentioning
confidence: 97%
“…5c ). GBF1 is recruited to the plasma membrane as punctae in CHO cells 34 and in AGS 38 cells that exhibit robust CG endocytosis. However, Hela cells do not show an obvious recruitment of GBF1 to the plasma membrane compared to CHO cells (Supplementary Fig 5d/e ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific function of endoA3 in CIE of CD166. In order to further characterize the molecular mechanisms of CD166 uptake, we focused on the endophilin-A (endoA) family of BAR domain proteins, which together with other members of the BAR domain protein superfamily, have already been implicated in CIE [2][3][4][25][26][27] . Interestingly, a strong inhibition of CD166 uptake was observed upon depletion of the A3 isoform of endophilin-A (endoA3) in HeLa cells, while no effect was observed upon depletion of the two other isoforms ( Fig.…”
Section: Quantitative Proteomics Of Cell Surface Upon Cme Inhibitionmentioning
confidence: 99%